Evaluation of the effect of soil and irrigation water characteristics on the chemical composition and antimicrobial activity of Mentha spicata L. essential oil: A plant used in traditional medicine of Kashan people - Vajiheh Gandomi Hosnaroodi; Mansureh Ghavam (Agricultural Water Management)
Plants containing essential oil may differ in performance and quality of essential oil based on the type of soil and water. Mentha spicata L. is one of the most important essential oil species of the lamiaceae family, which the people of Kashan use as a sedative, to treat flatulence, Intestinal and stomach diseases heartache are traditionally used. The present study was designed and carried out in order to evaluate and compare the composition, yield, and antimicrobial properties of the essential oil of this plant from 5 plain areas of Kashan (Lathor, Meshkat, Taher Abad, Issa Abad, and Fin) with different water and soil characteristics. For plant sampling, in August 2022, three points were randomly selected in each area, and then at each point, stems and leaves were randomly collected from different plants (150–200 plants at each point). After extracting the essential oils by water distillation (Clevenger) and determining the yield, the chemical compounds of the essential oils were identified by a chromatograph coupled with a mass spectrometer. To evaluate the antibacterial activity of the essential oil, the method of determining the diameter of the inhibition halo (IH) and determining the minimum concentration of growth inhibition (MIC) and killing of bacteria (MBC) was used. The analysis of variance showed that the effect of the region on the quantity, quality, and antimicrobial activity of M. spicata essential oil yield was significant (P ≤ 0.01). The highest and lowest yield of M. spicata essential oil belongs to the samples of Fin respectively (3.3 %) and Issa Abad (2.20 %). The highest number of compounds belonged to the essential oil of Lathor region equal to 50 compounds (99.98 %) and the lowest number of compounds related to the sample of Meshkat region was equal to 44 compounds (98.53 %). Based on the results, carvone (55.02–59.72 %) and limonene (18.57–15.31 %) were the first and second dominant compounds of M. spicata essential oil in all regions. The largest diameter of the halo of non-growth of M. spicata essential oil on Staphylococcus epidermidis (mm ∼ 21.50) was from the Issa Abad region, which has relatively good activity compared to the antibiotics. The most potent inhibitory and lethal effect of M. spicata essential oil belonging to the Tahir Abad region was against Candida albicans yeast (MIC and MBC=250 μg/mL), which was one order weaker compared to Nystatin (MIC =125 μg/mL). The selected essential oils may be a promising and potential strategy to achieve higher yields, higher carvene content and a possible natural option as an alternative to antibiotics against some strains.